Fresh Water Exploration in Gunung Tunak, Lombok Island, Using Wenner Electrodes Configuration - Muhammad Zuhdi; Syamsuddin Syamsuddin; Bakti Sukrisna; Teguh Ardianto; Agus Wahid Habiburrohman (Journal of Science and Science Education, 2023)
Geoelectric is the most popular geophysical method for groundwater exploration. This method is based on measuring the electric current injected into the earth and measuring the potential generated at the surface. This research was carried out at Mount Tunak, on the island of Lombok, using the Wenner electrode configuration. The data is then processed using the Res2div software. The survey was conducted on two lines and obtained two parameters, namely the injection electric current measured at the current electrode and the potential generated at the surface measured through the potential electrode. The measurement results show the rock resistivity values between 0.053 to 194 Ohm-meters. The resistivity of the aquifer rock has a value of 1.67 to 4.25 Ohm-meter, which is a sandy claystone with an aquifer containing fresh water at the depth of about 20 meters below the surface. There is a presence of salty water below the fresh water with resistivity between 0.102-0.657 Ohm-m.